Cutaneous myiasis in cats and dogs: Cases, predisposing conditions and risk factors - Marco Pezzi 1; Chiara Scapoli 1; Milvia Chicca 1; Marilena Leis 1; Maria Gabriella Marchetti 1; Carlo Nicola Francesco Del Zingaro 2; Chiara Beatrice Vicentini 1; Elisabetta Mamolini 1; Annunziata Giangaspero; Teresa Bonacci 4 (Veterinary Medicine and Science, 2020)
Two cases of cutaneous myiasis diagnosed in 2018 in Emilia-Romagna region (northern Italy) were reported. The first one, described in a domestic cat Felis silvestris catus L. (Carnivora: Felidae) and caused by Calliphora vicina Robineau-Desvoidy (Diptera: Calliphoridae), was the first one of this type ever reported in Italy in cats. The second one was described in a domestic dog Canis lupus familiaris L. (Carnivora: Canidae) and caused by Lucilia sericata (Meigen) (Diptera: Calliphoridae) and was unusual because it occurred in absence of lesions. An extensive literature search on cutaneous myiasis in these two domestic animal species was performed in order to draw attention to predisposing conditions and risk factors.